Hubungan Aktivitas Bauran Promosi Bistro dengan Keputusan Pembelian Konsumen - Syania Ismaya S.P; Mochammad Rochim (UNISBA Press, 2022)
Abstracts. Culinary tourism is growing quite rapidly, as evidenced by the increasing number of bistros and restaurants in Bandung every year. Talupa Bistro & Brunch is a new bistro that can compete with other bistros. Talupa Bistro & Brunch conducts promotional mix activities to increase sales volume through consumer purchasing decisions. This study was conducted to determine whether there is a relationship between the promotional mix activities of Talupa Bistro & Brunch which consists of advertising, sales promotion, direct marketing, and public relations with the consumer purchasing decisions of Talupa Bistro & Brunch. The theory used is the promotion mix theory, purchase decisions, and simple linear regression theory. This research uses correlation method. Data collection techniques by distributing questionnaires, interviews, literature study, and observation. Descriptive analysis techniques and inferential analysis Abstrak. Wisata kuliner berkembang cukup pesat, terbukti dengan meningkatnya jumlah bistro dan rumah makan di Kota Bandung setiap tahunnya. Talupa Bistro&Brunch merupakan salah satu bistro baru yang dapat bersaing dengan bistro lainnya. Talupa Bistro&Brunch melakukan aktivitas bauran promosi guna meningkatkan voume penjualan melalui keputusan pembelian konsumen. Penelitian ini dilakukan untuk mengetahui apakah terdapat hubungan antara aktivitas bauran promosi Talupa Bistro&Brunch yang terdiri dari advertising, sales promotion, direct marketing, dan public relations dengan keputusan pembelian konsumen Talupa Bistro&Brunch. Teori yang digunakan yaitu teori bauran promosi, keputusan pembelian, dan teori regresi linier sederhana. Penelitian ini menggunakan metode Korelasional. Teknik pengumpulan data dengan menyebarkan kuisioner, wawancara, studi pustaka, dan observasi. Teknik analisis deskriptif dan analisis inferensial.